Effect of Screw Speed, Drawing Ratio and PET Concentration on the Properties of PET/PP Blends - Erkoc, I. Gokgoz; Guven, T.; Yildirim, F.; Sozer, M.; Guner, F. (POLISH ACAD SCIENCES INST PHYSICS, 2018)
The objective of this study is to investigate the influence of screw speed, drawing ratio and composition of blend on the morphology and the mechanical properties of extruded and drawn PET/PP blends. Samples were generated by a two-step process. Firstly, PET was dispersed in PP matrix at different extrusion screw speeds in order to determine optimum mixing condition, and then extrudates were stretched by a take up device. Final morphology and mechanical properties of the samples were examined using scanning electron microscopy, dynamic mechanical analysis, and a universal testing machine. The results showed that low screw speeds were not enough to distribute PET droplets homogeneously inside the matrix. With increasing of the screw speed more homogeneous phase morphology was obtained but further increase caused to agglomeration of PET droplets. Scanning electron microscopy images also showed that with increasing of draw ratio PET droplets changed from spherical to rod-like shape, and finally to microfibrils in matrix. It was also found that with increasing of concentration of PET and draw ratio, mechanical properties increased up to 6-7 times compared to non-oriented samples.
Keywords: polymer blend; drawing; fibrillation; polypropylene; polyethylene terephthalate; MICROFIBRILLAR-REINFORCED COMPOSITES; MORPHOLOGY; POLYMER; BEHAVIOR; Physics